Правова природа договору страхування - Nykyforak, Volodymyr; Никифорак, Володимир Михайлович (Чернівецький національний університет. Видавництво "Рута"., 2005)
In the article are disclosed value and features of insurance contract in modern market situation. Besides the author analyses the essential conditions of the insurance contract
Keywords: страхування; договір